Kondisi Ovarium dan Saluran Reproduksi Setelah Pemberian Cahaya Monokromatik pada Puyuh (Coturnix coturnix japonica) - Desly, Desly; Saraswati, Tyas Rini; Mardiati, Siti Muflichatun (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
Quail Product (Coturnix coturnix japonica) in the form of meat and eggs is a variation of the source of animal protein for human consumption. Like other poultry cultivation of intensive, maintaining the scale cultivation of quail in need of maintenance and good governance to obtain maximum results and profitable. One of the important things in a maintenance program is a good quail cage lighting. Quail is an organism that is sensitive to stimuli of light, light is required to regulate various biological processes, including the reproductive system. Light energy can be obtained from natural and artificial light. This research aims to use artificial light, which is monochromatic light to obtain basic information about aspects of the reproductive system of quail regarding the condition of the ovaries and reproductive tract. Monochromatic light is a type of visible light with the frequency of a single wavelength. Treatment consists of lighting from above 4 groups, namely the use of monochromatic light LED lights red, green, and blue with 15 lux and the light intensity control using a 15 watt incandescent bulb. All treatments began at 4-week-old quail to 9 weeks, from 5:00 p.m. to 07:00 o'clock. The parameters in this study were ovarian weight, number of hierarchical follicles, length and weight of the reproductive tract. This study using Completely Randomized Design (CRD) with replications is not the same. Data generated in this study were analyzed using the Analysis Of Variance (ANOVA) if there is a real difference then conducted further tests duncan. The results of this study showed that monochromatic light of red, green, and blue can affect ovarian weight and the weight of the reproductive tract, but has not given a real influence on the length of the reproductive tract and the number of follicles. In conclusion, the artificial light in the form of monochromatic light can be used as an alternative to the cultivation of quail to produce an optimal product.